INTEGRATED EDUCATION FOR MUSIC PEDAGOGY STUDENTS IN UKRAINE AND CHINA - Yue , Wu (The Modern Higher Education Review, 2023)
The article examines the issue of modernization of music education and pedagogy in Ukraine and the People’s Republic of China from the point of view of the implementation of the integrated principle of education. The ways of implementing integration in the content of music education of the two countries in school and university education are outlined. The role of a competent approach to the training of a music teacher capable of solving the tasks offered by the real conditions of the modern world is determined. The role of artistic and pedagogical analysis for work with students of the speciality 014 Secondary Education (Musical Art) is revealed. Specific examples of methods of implementation of the training of students to work with students in conditions of integrated education are given. The multidimensionality of the process of formation of polyphonic knowledge of music pedagogy students is analysed from the point of view of multidisciplinary integration. The components of education and training of music pedagogy students in Ukraine and the People’s Republic of China are substantiated, in accordance with the implementation of the ideas of new standards of school and higher education. The peculiarities of the selection of educational material for its practical mastery with the students based on the interdisciplinary integration of art lessons are given. The peculiarities of mastering musical works from operas by Chinese students in Ukrainian pedagogical universities using the integrated method of modelling the artistic and creative process are revealed.